2020
DOI: 10.1186/s12891-020-3097-8
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, classification, treatment and mortality of distal radius fractures in adults: an observational study of 23,394 fractures from the national Swedish fracture register

Abstract: Background: Distal radius fractures are the most common of all fractures. Optimal treatment is still debated. Previous studies report substantial changes in treatment trends in recent decades. Few nationwide studies on distal radius fracture epidemiology and treatment exist, none of which provide detailed data on patient and injury characteristics, fracture pattern and mortality. The aim of this study was to describe the epidemiology, fracture classification, current treatment regimens and mortality of distal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
133
10
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(163 citation statements)
references
References 35 publications
(47 reference statements)
9
133
10
11
Order By: Relevance
“…The main surgical methods for distal radius fractures (DRFs) include open reduction with internal fixation (ORIF) using a volar plate (plate); closed reduction with percutaneous pinning (pins); and closed reduction with external fixation (EF). While a majority of all DRFs can be managed non-surgically, about 20% are treated surgically [1,2]. Recent studies have reported that the proportion of surgically managed fractures is increasing, and that the preferred surgical method has shifted from percutaneous techniques to ORIF over the last two decades [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The main surgical methods for distal radius fractures (DRFs) include open reduction with internal fixation (ORIF) using a volar plate (plate); closed reduction with percutaneous pinning (pins); and closed reduction with external fixation (EF). While a majority of all DRFs can be managed non-surgically, about 20% are treated surgically [1,2]. Recent studies have reported that the proportion of surgically managed fractures is increasing, and that the preferred surgical method has shifted from percutaneous techniques to ORIF over the last two decades [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The Swedish Fracture Register (SFR), on the other hand, prospectively collects data on all patients with all types of fracture, regardless of treatment [ 10 , 11 ]. Several validity and epidemiological studies based on data from the SFR have been published [ 1 , 12 21 ]. Register-based studies, such as studies based on data from the SFR, include all patients and fractures, regardless of treatment, and can describe the current treatment and results of the treatment algorithms being used in current clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Distal radius fractures constitute a social problem [1][2][3][4][5][6][7][8][9][10][11][12][13]. The COVID-19 pandemic has had a considerable impact on the lives of both adults and children around the world [13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Distal radius fractures (DRFs) constitute 15-21% of all fractures and are the third most common location of osteoporosis-related fractures [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The estimated risk of DRF is 9-139/10,000 people per year [3,4,8,11,12].…”
Section: Bacgroundmentioning
confidence: 99%
See 1 more Smart Citation